2006
DOI: 10.1111/j.1420-9101.2005.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of sex pheromone blend differences between Heliothis virescens and Heliothis subflexa: a chromosome mapping approach

Abstract: Males of the noctuid moths, Heliothis virescens and H. subflexa locate mates based on species‐specific responses to female‐emitted pheromones that are composed of distinct blends of volatile compounds. We conducted genetic crosses between these two species and used AFLP marker‐based mapping of backcross families (H. subflexa direction) to determine which of the 30 autosomes in these moths contained quantitative trait loci (QTL) controlling the proportion of specific chemical components in the pheromone blends.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 86 publications
(140 reference statements)
6
69
1
Order By: Relevance
“…Finally, quantitative variation of the principal CHC, (Z)-11-pentacosene, between a genetically marked strain of D. virilis and D. novamexicana segregated with two of the six chromosomes and one major genetic factor was mapped (Doi et al, 1996; for a review of Drosophila work, see Ferveur, 2005;Gleason et al, 2005). This polygenic basis is also found for female differences in long-range pheromone compounds between H. virescens and H. subflexa (Groot et al, 2004;Sheck et al, 2006).…”
Section: Genetics Of Divergence In Chemical Signalsmentioning
confidence: 91%
“…Finally, quantitative variation of the principal CHC, (Z)-11-pentacosene, between a genetically marked strain of D. virilis and D. novamexicana segregated with two of the six chromosomes and one major genetic factor was mapped (Doi et al, 1996; for a review of Drosophila work, see Ferveur, 2005;Gleason et al, 2005). This polygenic basis is also found for female differences in long-range pheromone compounds between H. virescens and H. subflexa (Groot et al, 2004;Sheck et al, 2006).…”
Section: Genetics Of Divergence In Chemical Signalsmentioning
confidence: 91%
“…Indeed, case studies indicating an absence of genetic coupling abound. For instance, in several species of moth, including the almond moth (6), adzuki borer moth (7), corn borer moth (8), and heliothine moths (9,10), it is quite clear that the female pheromone signal and male response are under separate genetic control. Similarly, male and female mating behaviors in Drosophila arizonensis and Drosophilia mojavenis have distinct genetic bases (11), as do pheromone production and response in the pine engraver beetle (12).…”
Section: Disentangling Coevolution and Genetic Couplingmentioning
confidence: 99%
“…These two species are not attracted to each other in field locations where they cooccur because of differential response to pheromone blends (28), but they can be mated and backcrossed in the laboratory (28). Our previous quantitative trait locus (QTL) studies with backcross (BC) families demonstrated that genes on at least nine of the 31 Heliothis chromosomes contribute to the differences between the species in the volatile compounds produced by the pheromone gland and indicate that there can be epistatic interactions among the QTL (29,30). In the current experiments, we used a combined QTL/candidate gene approach to determine what classes of genes code for the differences between males of the two species in their response to pheromone blends.…”
mentioning
confidence: 99%
“…Heliothis virescens (hereafter referred to as Hv) is a generalist, feeding on plants in over 14 families, whereas Heliothis subflexa (Hs) specializes on plants within the genus Physalis (28,29). These two species are not attracted to each other in field locations where they cooccur because of differential response to pheromone blends (28), but they can be mated and backcrossed in the laboratory (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation